Porous monolith of few-layered boron nitride for effective water cleanup. Issue 2 (17th December 2021) - Xu, Chenyang; Zeng, Jinjue; Gu, Xianrui; Wang, Yue; Li, Erchun; Zhang, Chen; Ge, Cong; Jin, Cheng; Miao, Meng; Jin, Zhu; Gao, Tian; Jiang, Xiangfen; et al.
Abstract : The porous monolith of boron nitride is manufactured via a borax-based pyrolysis route, which demonstrates high sorption performance on pollutants for water purification. Abstract : Advanced sorbents for water purification need to be developed for environmental protection. Porous boron nitride (BN) is a high-end material for the removal of pollutants for its remarkable sorption characteristics and chemical inertia. However, it still suffers from thick pore walls, low yield and powdery state, limiting the performance. Herein, a borax-based template-free pyrolysis route is developed to massively produce the cellular monolith of a few-atomic-layered boron nitride. It possesses ultra-thin pore walls and uniform mesopores, resulting from the phase-separation-dominated pore-forming mechanism. Such a porous monolith is applied for water purification, showing high adsorption capacity on Congo red (1096 mg g −1 ), which is attributed to mesopores and surface polarity. It further exhibits unprecedented recyclability, relying on its anti-oxidation stability. A prototype of the water filter pitcher using this BN is finally demonstrated with commendable performances. The aerogel-like BN bulk material enables a high-capacity recyclable sorbent, representing a leap forward toward practical water purification.